Antecedents of Career Adaptability in Strategic Career Management. (May 2017) - Chong, SinHui; Leong, Frederick T. L.
Career adaptability is an important characteristic that helps individuals deal effectively with career uncertainty and ambiguous job roles in current times. Based on the career construction theory, we hypothesize that conscientiousness, cognitive flexibility, and environmental exploration are positively related to career adaptability, and career adaptability is in turn positively related to strategic career management. We collected data from 307 undergraduates with work experience to test our hypothesized model. The results generally supported our hypotheses. Our research sheds light on how conscientiousness, cognitive flexibility, and environmental exploration are related to strategic career management indirectly through career adaptability. Our findings offer practical advice for vocational scholars and career counselors on how career adaptability may be developed.